Anterior deprogramming device as an interim appliance for clinical and occlusal stabilization during a digital workflow occlusal device design: A clinical report with an 18-month follow-up - de Oliveira, Juliana Ignacio; de Oliveira, Simone Saldanha Ignacio; Zambrana, Nataly; Morales, Marvin Luis Mendoza [UNESP]; Sesma, Newton; Laganá, Dalva Cruz (Elsevier, 2025)
The fabrication of digital occlusal devices requires registering a correct maxillomandibular relationship that relies on the concepts of centric relation or adapted centric posture. A technique using an acrylic resin anterior deprogramming device was used as an initial treatment. This device relieved acute temporomandibular disorder symptoms and acted as an initial trial, promoting posterior disocclusion, functioning as a neuromuscular reprogramming aid, and simultaneously allowing the clinician to test the patient's neuromuscular engram on the device's definitive thickness. A digital workflow was used for the subsequent treatment to deliver an individualized occlusal device according to the patient's neuromuscular engram. Advantages of the device included the rapid management of acute pain and the alignment of the maxillomandibular relationship during intraoral scanning.